The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-19126-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Serjania erecta on the development of Chrysodeixis includens

Abstract: The soybean looper, Chrysodeixis includens, is a primary soybean pest that reduces crop productivity. This work examined control of C. includens populations with methanolic extract of Serjania erecta, a native Cerrado plant, while minimizing risks to pollinators, natural enemies and the environment. Serjania erecta specimens were collected, identified, and subjected to methanol extraction. Bioassays were performed using newly hatched and second-instar caterpillars and different extract concentrations on the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Other trials have shown nematicidal effects against Pratylenchus zeae and P. jaehni ( Slomp et al, 2009 ), as well as antimicrobial effects against key human pathogens, including Mycobacterium tuberculosis , Staphylococcus aureus , Pseudomonas aeruginosa , Salmonella setubal , Candida albicans , Saccharomyces cerevisiae , and Escherichia coli ( Cardoso et al, 2013 ). Metabolites present in S. erecta can also affect insects, as it directly interferes with the growth, metabolism, and development of caterpillars ( De Freitas et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other trials have shown nematicidal effects against Pratylenchus zeae and P. jaehni ( Slomp et al, 2009 ), as well as antimicrobial effects against key human pathogens, including Mycobacterium tuberculosis , Staphylococcus aureus , Pseudomonas aeruginosa , Salmonella setubal , Candida albicans , Saccharomyces cerevisiae , and Escherichia coli ( Cardoso et al, 2013 ). Metabolites present in S. erecta can also affect insects, as it directly interferes with the growth, metabolism, and development of caterpillars ( De Freitas et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%